Menentukan Nilai Penggantian Wajar Lahan Terdampak Pekerjaan Reaktifasi Jalur Kereta Api Trase Muaro Logas, Kabupaten Sijunjung, Provinsi Sumatera Barat - Asymar, Hasta Herlan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract  – The calculation of the value of the Reasonable Land Turnover Terdamapak Job Reaktifasi railway line for arbitration was Muaro Logas was part of the study of the action of liberation/land and buildings for the reform plan of the reaktifasi railway line between Muaro-Logas is part of the planning of the reactivation railway line. This study analyzes regulations and policies, perceived an inventory and survey/census by identifying the affected community land procurement, with regard to the characteristics and the types of harm experienced, agreement agreement between the local government, the province and the Center in funding the acquisition of land; analyze optimum land procurement and analyse livelihood for the population affected by socio-economic factors, analyzing the parameters with the social, cultural, and economic related to population, the impact of the procurement of land and influence implementation of the work against the poor, residents of the tribal minorities, alienated, and other vulnerable groups, including women, as well as the institutional framework in planning the liberation of land and the settlements back including duties and responsibilities each institution. In the calculation of the Reasonable Replacement Value using Standar Penilaian Indonesia306 (SPI 306) about the assessment of the provision of Land for development for the benefit of the public